Why, when and how do secondary-care clinicians have emergency care and treatment planning conversations? Qualitative findings from the ReSPECT Evaluation study. (May 2021) - Eli, Karin; Hawkes, Claire A.; Ochieng, Cynthia; Huxley, Caroline J.; Baldock, Catherine; Fortune, Peter-Marc; Fuld, Jonathan; Perkins, Gavin D.; Slowther, Anne-Marie; Griffiths, Frances
Abstract: Background: The Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) is an emergency care and treatment planning (ECTP) process, developed to offer a patient-centred approach to deciding about and recording treatment recommendations. Conversations between clinicians and patients or their representatives are central to the ReSPECT process. This study aims to understand why, when, and how ReSPECT conversations unfold in practice. Methods: ReSPECT conversations were observed in hospitals within six acute National Health Service (NHS) trusts in England; the clinicians who conducted these conversations were interviewed. Following observation-based thematic analysis, five ReSPECT conversation types were identified: resuscitation and escalation; confirmation of decision; bad news; palliative care; and clinical decision. Interview-based thematic analysis examined the reasons and prompts for each conversation type, and the level of detail and patient engagement in these different conversations. Results: Whereas resuscitation and escalation conversations concerned possible futures, palliative care and bad news conversations responded to present-tense changes. Conversations were timed to respond to organisational, clinical, and patient/relative prompts. While bad news and palliative care conversations included detailed discussions of treatment options beyond CPR, this varied in other conversation types. ReSPECT conversations varied in doctors' engagement with patient/relative preferences, with only palliative care conversations consistently including an open-ended approach. Conclusions: While ReSPECT supports holistic, person-centred, anticipatory decision-making in some situations, a gap remains between the ReSPECT's aims and their implementation in practice. Promoting an understanding and valuing of the aims of ReSPECT among clinicians, supported by appropriate training and structural support, will enhance ReSPECT conversations.